If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(w + -12) + 30 = w Reorder the terms: 3(-12 + w) + 30 = w (-12 * 3 + w * 3) + 30 = w (-36 + 3w) + 30 = w Reorder the terms: -36 + 30 + 3w = w Combine like terms: -36 + 30 = -6 -6 + 3w = w Solving -6 + 3w = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. -6 + 3w + -1w = w + -1w Combine like terms: 3w + -1w = 2w -6 + 2w = w + -1w Combine like terms: w + -1w = 0 -6 + 2w = 0 Add '6' to each side of the equation. -6 + 6 + 2w = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2w = 0 + 6 2w = 0 + 6 Combine like terms: 0 + 6 = 6 2w = 6 Divide each side by '2'. w = 3 Simplifying w = 3
| -2x^2+7x-3=0 | | 11x-31=5x+5 | | 6x+37=8x-9 | | 0.5x+2+3=9x+1.5x | | 0.5x+2+3=9x+105x | | 5r-4-6=-20 | | -3(x-11)=21x | | 4x+13=-91-9x | | 150=-9x-6x | | 8+x=19 | | 7-8p-5p=20 | | 3x=5.500 | | -30=3n-12n | | .600t=-12 | | -3.500w=20 | | 3x+5=32 | | 2(2x+5)=5(2x-2) | | 1.250x=.5 | | -x-7=10 | | .667m=7 | | 3x+7=-2x+1 | | 143-5x=5x+13 | | 3x+7=2x+1 | | 8y-9y=4 | | 35z+12=82 | | -75x+5=230 | | 33b-3=96 | | 2r+45=15 | | 9y-11=-38 | | 19b-4=72 | | 2x+5x-3x-3=9 | | -3x+5y=-5 |